A systematic review of the traits and cognitions associated with use of and belief in complementary and alternative medicine (CAM). Issue 7 (9th August 2018) - Galbraith, Niall; Moss, Tim; Galbraith, Victoria; Purewal, Satvinder
Abstract: Complementary and alternative medicine (CAM) use is widespread despite the controversy over its effectiveness. Although previous reviews have examined the demographics and attitudes of CAM users, there is no existing review on the traits or cognitions which characterise either CAM users or those who believe in CAM effectiveness. The current systematic review set out to address these gaps in the literature by applying a narrative synthesis. A bibliographic search and manual searches were undertaken and key authors were contacted. Twenty-three papers were selected. The trait openness to experience was positively associated with CAM use but not CAM belief. Absorption and various types of coping were also positively associated with CAM use and belief. No other trait was reliably associated with CAM use or belief. Intuitive thinking and ontological confusions were positively associated with belief in CAM effectiveness; intuitive thinking was also positively associated with CAM use. Studies researching cognitions in CAM use/belief were mostly on non-clinical samples, whilst studies on traits and CAM use/belief were mostly on patients. The quality of studies varied but unrepresentative samples, untested outcome measures and simplistic statistical analyses were the most common flaws. Traits and cognition might be important correlates of CAM use and also of faith in CAM.